The potential of the integrated project-based and 4C-scaffolding (Pj4CS) learning model to increase prospective biology teachers’ global 4C skills - Muh.Amin, Astuti; Karmila, Fitriyah; Adiansyah, Romi; Mustami, Muhammad Khalifah; Hujjatusnani, Noor; Parmin, Parmin (Journal of Turkish Science Education, 2026)
Research on identifying 4C skills using the Pj4CS model remains limited, especially in biology education. Preliminary studies indicate that the 4C skills of prospective biology teachers still need improvement and optimal utilization in classroom learning. This study aims to analyze the potential of the Integrated Project-Based and 4C-Scaffolding (Pj4CS) model to increase global 4C skills (Critical Thinking, Communication, Collaboration, and Creativity). This research type is a quasi-experiment. The research instrument was valid and reliable before data collection. The research results showed differences in 4C skills between the pretest and posttest in the Pj4CS model. The t-test results showed significance at the 0.000 level for critical thinking, communication, collaboration, and creativity. A significance value of less than 0.05 indicated that the Pj4CS model effectively improved students’ critical thinking, communication, collaboration, and creativity. Providing appropriate scaffolding in project-based learning helps students produce more creative project products. The Pj4CS model has been shown to positively impact improving aspects of critical thinking, communication skills, collaboration skills, and creativity, which are important life skills that must be developed in today's learning. Students are trained to develop critical thinking and communication skills through collaborative project design. The syntax of the Pj4CS model positively empowers 4C skills in biology learning. The research concludes that the Pj4CS model can improve 4C global skills (critical thinking, communication, collaboration, and creativity).
Keywords: critical thinking skills; communication; Pj4CS Model